2018
DOI: 10.1210/en.2018-00097
|View full text |Cite
|
Sign up to set email alerts
|

MiR-7 Mediates the Zearalenone Signaling Pathway Regulating FSH Synthesis and Secretion by Targeting FOS in Female Pigs

Abstract: Zearalenone (ZEA) acts as an environmental endocrine disruptor (EED) to cause health detriments. miRNAs were reported to influence the synthesis and secretion of pituitary hormones. However, the interactions between ZEA and miRNAs and related mechanisms remain unclear. The aims of this study were to determine whether and how miR-7 affects animal reproduction by its interactions with ZEA in the pig pituitary, which is sensitive to ZEA and has been used as an important animal model in medical research. Expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…The present study shows that the RAF1 stimulates E 2 synthesis and secretion via FSH signaling pathway in mouse GCs. Previous reports have shown that RAF involved in the regulation of steroid hormone synthesis via ERK1/2 [23] or affected the functions of steroid hormones and their receptors [25], and its interacted with microRNA [24]. The present study demonstrated RAF1 acted as a molecule of FSH pathway to trigger the ERK phosphorylation and stimulate GCs estradiol synthesis and secretion events.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The present study shows that the RAF1 stimulates E 2 synthesis and secretion via FSH signaling pathway in mouse GCs. Previous reports have shown that RAF involved in the regulation of steroid hormone synthesis via ERK1/2 [23] or affected the functions of steroid hormones and their receptors [25], and its interacted with microRNA [24]. The present study demonstrated RAF1 acted as a molecule of FSH pathway to trigger the ERK phosphorylation and stimulate GCs estradiol synthesis and secretion events.…”
Section: Discussionsupporting
confidence: 59%
“…Previous reports have shown that RAF1 receives extracellular signals [18] and functions in RAS pathway to transmit signals to the downstream kinases MEK and ERK [19], whereas RAF1 is activated by the binding small G proteins of the RAS family to the N-terminal region of the RAF proteins [20], and activated RAF1 subsequently activates MEK (MAP kinase kinase), MAP kinase [21], and also activates other downstream kinases and transcription factors [22]. In addition, it has been reported that RAF is a critical for steroidogenesis via ERK1/2 [23], and our recent study shows that RAF1 is a vital downstream signal in microRNA regulating process of pituitary hormone [24]. These collective data suggest that RAF1 is involved in the regulation of steroid hormone synthesis, which makes us to hypothesize whether RAF1 is involved in FSH signaling pathway to regulate E 2 synthesis and secretion in mouse GCs.…”
Section: Introductionmentioning
confidence: 80%
“…Numbers of studies also revealed several of their enrichment and function. MiR-7 is abundant in the pituitary of mouse [111], pigs [112,113]. Research showed that miR-7 might play an important role in the HPG axis and be involved in body growth by acting on the pituitary(GHRHR) in pigs [112,114].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-7 is abundant in the pituitary of mouse [111], pigs [112,113]. Research showed that miR-7 might play an important role in the HPG axis and be involved in body growth by acting on the pituitary(GHRHR) in pigs [112,114]. MiR-375 could regulate pituitary pro-opiomelanocortin (POMC) expression [115].…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of hematological and biochemical measures, gene expression and subpopulations of immunocompetent cells in tissues have been observed after ZEN exposure in piglets and prepubertal gilts, albeit with limited reproducibility between studies [7]. Recently, the effect of ZEN on the expression of microRNAs has caught scientific interest [8,9,10,11]. MicroRNAs represent a class of small non-coding RNAs, that negatively regulate gene expression.…”
Section: Introductionmentioning
confidence: 99%